Magmatisme dan Vulkanisme : Literature Review - Nugroho Marsiyanto; Edy Soesanto; Aly Rasyid (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
Magmatism and volcanism represent two fundamental geological processes that play a crucial role in the internal dynamics of the Earth and the formation of igneous rocks. Magmatism encompasses all processes related to magma generation as a result of partial melting of the mantle or crust, including magma migration, differentiation, and crystallization beneath the Earth's surface. Volcanism, in contrast, constitutes the surface expression of magmatic activity, occurring when magma ascends through volcanic conduits and erupts at the surface, producing lava flows, pyroclastic materials, and volcanic gases. Although genetically related, these processes differ significantly in their spatial occurrence, mechanisms, and geological products. This study aims to elucidate the conceptual and process-based differences between magmatism and volcanism and to examine their interrelationship within the Earth’s geodynamic system. The research adopts a literature-based methodology, reviewing peer‑reviewed publications from accredited national and international journals in geology and volcanology. Secondary data analyzed include studies on magma generation, magma chamber dynamics, intrusive magmatic systems, and volcanic eruption mechanisms as addressed in contemporary geological research. The results indicate that magmatism predominantly occurs beneath the Earth’s surface and forms intrusive bodies such as batholiths, laccoliths, sills, and dikes through magma crystallization before reaching the surface. Volcanism, on the other hand, represents the extrusion of magma at the surface and plays a fundamental role in the development of volcanoes and volcanic landscapes. A comprehensive understanding of the relationship between magmatism and volcanism is essential for interpreting crustal evolution, mineral resource exploration, and the mitigation of geological hazards associated with volcanic activity.